2017
DOI: 10.3389/fpsyg.2017.00703
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gender Stereotypes on the Self-Concept of Female Students in STEM Subjects with an Under-Representation of Females

Abstract: It's possible to assume that women who study STEM topics with a low proportion of females have successfully overcome barriers in school and the family, making them less prone to stereotypic views, and influences. The present study focuses on these kinds of factors and analyzes to which degree family factors, school-related factors, and individual stereotypes may influence a woman's academic self-concept. The following study presents a latent regression model which is based on a survey of 296 women from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(147 citation statements)
references
References 39 publications
3
134
3
7
Order By: Relevance
“…Pinxten et al (2014), por exemplo, observaram que os alunos que se percecionavam como menos competentes reportavam dedicar um maior esforço às atividades na matemática. Podemos inferir que o facto de as raparigas se percecionarem como menos competentes na matemática impele-as a trabalharem mais e a envolverem-se mais nas tarefas de matemática (Brown & Kanyongo, 2010) obtendo um desempenho académico semelhante ao dos rapazes, mitigando assim a lacuna que existia entre rapazes e raparigas ao nível da PC na matemática (Ertl, Luttenberger, & Paechter, 2017). Também no estudo realizado por Mata et al (2012) com alunos do ensino básico, os autores constataram que raparigas e rapazes tinham desempenhos iguais e as raparigas percecionavam-se como menos competentes; contudo, atribuíam mais valor à matemática.…”
Section: O N C Lu S õ E Sunclassified
See 1 more Smart Citation
“…Pinxten et al (2014), por exemplo, observaram que os alunos que se percecionavam como menos competentes reportavam dedicar um maior esforço às atividades na matemática. Podemos inferir que o facto de as raparigas se percecionarem como menos competentes na matemática impele-as a trabalharem mais e a envolverem-se mais nas tarefas de matemática (Brown & Kanyongo, 2010) obtendo um desempenho académico semelhante ao dos rapazes, mitigando assim a lacuna que existia entre rapazes e raparigas ao nível da PC na matemática (Ertl, Luttenberger, & Paechter, 2017). Também no estudo realizado por Mata et al (2012) com alunos do ensino básico, os autores constataram que raparigas e rapazes tinham desempenhos iguais e as raparigas percecionavam-se como menos competentes; contudo, atribuíam mais valor à matemática.…”
Section: O N C Lu S õ E Sunclassified
“…Da mesma forma, examinar a relação entre estes preditores e o desempenho na matemática em rapazes e raparigas ao longo dos anos escolares poderá fornecer uma visão mais precisa dos processos subjacentes que levam a diferenças posteriores no desempenho na matemática como os identificados nas provas do PISA (OECD, 2013(OECD, , 2016. Os resultados deste estudo levam-nos a refletir sobre o efeito que os pais e professores têm na construção da PC na matemática das raparigas, tornando-se necessário sensibilizar e consciencializar os pais e, sobretudo, os professores para a existência desses estereótipos sociais e dos seus efeitos nefastos, contribuir para a sua desconstrução e ajudar os professores a encontrar estratégias pedagógicas promotoras de oportunidades para as raparigas vivenciarem experiências positivas em relação à matemática que não reforcem o estereótipo social (Ertl et al, 2017). Estimular os sentimentos e crenças dos alunos relativamente às suas reais competências na matemática poderia levar, no caso das raparigas, a um maior prazer e satisfação na realização das tarefas de matemática.…”
Section: R E F E Rê N C Iasunclassified
“…In the investigation of 584 high school students in Taiwan, Tien, Wang, and Liu (2009) found that female students perceived more barriers than male students regarding gender discrimination in the process of career decision-making. Similarly, Bernhard, Silke, and Manuela (2017) reported that gender stereotypes were negatively related to students' STEM career planning in their survey of 296 German female students. Moreover, our results are consistent with May and Chubin's (2003) findings that the success of minority students in STEM is related to admission policies and financial assistance.…”
Section: Personal Inputmentioning
confidence: 98%
“…While EVT describe the complex interactions of this moderation process (see Eccles et al, 1983), SCCT rather focuses the steps from the individual's personal inputs toward choice actions moderated by expectancies and contextual factors. These are especially important for female students' career paths into STEM because cultural stereotypes of STEM as a "male" domain as well as interactions with teachers and significant others may influence women to steer away from STEM to more "female" domains or to not consider a STEM career at all (see Ertl et al, 2017).…”
Section: Gendered Paths Into Stem Disparities Between Females and Mamentioning
confidence: 99%
“…Although the term STEM raises the impression of being a homogeneous academic domain, there are different definitions which vary in their broadness and some of them even include life sciences and social sciences into STEM (for a discussion, see Ertl et al, 2017). This Research Topic focuses on the core of STEM that covers natural sciences, technology, engineering, and mathematics.…”
Section: Heterogeneity Of Stem Subjectsmentioning
confidence: 99%